PENGARUH PERSONAL VALUES TERHADAP PENGAMBILAN KEPUTUSAN ETIS AKUNTAN PUBLIK - Ario, Ugung Dwi; Pramono, Hadi (AMONG MAKARTI, 2009)
Ethical reasoning has recently received conciderable emphasis in the accounting literature. Values are believed to be a powerful force behind on the behavioral responses of individuals. Individual values play an important role in influencing the behavior and ethical decision making, but several studies have failed to provide support for effect of individual values on ethical decision making in bussines. The purpose of this study is to evaluate whether in individual values explain differing perception of moral intensity when moral agent are confronted with the same issue. Subject of this study were 100 accountant. Sample determined by purposive sampling to accountant with two years experiance.. Regression analysis was used to test hypotheses regarding relationships between values and perception of moral intensity. This study results there are not influence of individual values on respondents’ perception of moral intensity. There is the possibility that the nature of the study topic (ethics) must have detracted from influence of personal values as determinants of ethical behavior. Limitations exist when students are used as subjects. Key words: ethical behavior, individual values, perception of moral intensity